2016
DOI: 10.21608/jfds.2016.42822
|View full text |Cite
|
Sign up to set email alerts
|

Using Whey Protein Isolate as a Substitute of Milk Solid Not Fat on Chemical and Physico-Chemical Properties of Ice Cream

Abstract: Effect of whey protein isolate (WPI) as a partial substitution of milk solids not fat (MSNF) in ice cream formula was investigated by replacing 1, 2, 3 and 4% of mix solid not fat. Mixes and resultant ice cream samples were evaluated for their chemical, physico-chemical, as well as the sensory quality attributes. There was no remarkable effect of adding WPI as partial substitution of skim milk powder (SMP) on total solids or fat percentages, while total protein, ash, and lactose content were significantly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Akalin et al (2008) reported that the addition of 4% whey protein isolate increased the hardness of low-fat ice creams. El-Zeini et al (2016) observed a decrease in the melting velocity in ice cream due to the substitution of skim milk powder with whey protein isolate powder at 4%. Nevertheless, in our study, RW ice creams had similar overall liking to the commercial sample and higher (P < 0.05) scores for this parameter compared with 100% WM.…”
Section: Sensory Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Akalin et al (2008) reported that the addition of 4% whey protein isolate increased the hardness of low-fat ice creams. El-Zeini et al (2016) observed a decrease in the melting velocity in ice cream due to the substitution of skim milk powder with whey protein isolate powder at 4%. Nevertheless, in our study, RW ice creams had similar overall liking to the commercial sample and higher (P < 0.05) scores for this parameter compared with 100% WM.…”
Section: Sensory Analysismentioning
confidence: 97%
“…Furthermore, each level and type of dairy by-product will determine different effects on the final product due mainly to specific interactions with the other food ingredients (Morin et al, 2006;Bald et al, 2014;Cortellino and Rizzolo, 2018). Nevertheless, previous studies already reported a decrease in the melting velocity of ice cream with the addition of 4% whey protein isolate in substitution for skim milk (El-Zeini et al, 2016), an increase of chocolate flavor perception in dairy beverage due to the addition of 15 and 45% cheese whey (da Silveira et al, 2015), as well as an increase of percep- tion of sweetness and orange flavor athletic drink with the addition of 66.67% cottage cheese whey (Crippen and Jeon, 1984). Principal Component Analysis and Partial Least Squares Regression.…”
Section: Sensory Analysismentioning
confidence: 99%
“…Additionally, camel milk fat contains higher content of cholesterol (34.5 mg/100g) than that of bovine milk (25.63 mg/100g) (Nahar et al, 2016). The size of camel milk fat globules is about 2.99 µm, which was smaller than the buffalo and cow milk fat globules 8.7 µm, while similar to the goat milk 3.19 µm; these unique features contributed to the white color of camel milk (Al Kanhal, 2010;El-Zeini, 2006). Camel milk is naturally whiter than cow's milk.…”
Section: Chemical Composition Of Camel Milkmentioning
confidence: 99%
“…Moreover, these same authors reported that 100% of whole milk's replacement by 100% cheese whey only resulted in higher JAR for cream color and sweetness, while butter whey ranging from 25% to 100% led to higher JAR for cream aroma and cream flavor. El-Zeini et al [35] observed that 4% whey protein isolate in replacement to skimmed milk decreased ice cream's melting velocity. Silveira et al [36] found an increased perception of chocolate flavor by adding 15% and 45% cheese whey in the dairy beverage.…”
Section: Just-about-right (Jar) and Penalty Analysismentioning
confidence: 99%